Experiences in a Clinical Innovation Pharmacy Fellowship: A Novel Model of Ambulatory Care Training and Practice Advancement - Alison Doane; Nicholas Cox; Shannon Gadd; Erin Gurney; Payson Ashmead; Kyle Turner (Pharmacy)
The University of Utah Clinical Innovation Fellowship models novel partnerships between third-party payers, clinical practices, and academia. While healthcare costs continue to increase unabated and physician burnout leads to provider shortages, this fellowship focuses on both crises by training pharmacists to establish new practices in ambulatory clinic spaces using funding provided by third-party payers. Not only does this fellowship represent a future in which pharmacists are able to address third-party payers’ need to reduce healthcare costs and clinics’ need to address provider shortages, it also successfully trained fellows to pursue jobs in ambulatory care and academia. Payers, clinics, providers and patients all expressed a high degree of satisfaction with the work of the fellows. In multiple clinics where fellows established new pharmacy services, those services led directly to new job approvals funded by the clinics themselves. The purpose of this paper is to serve as a model by which fellowship programs elsewhere can be designed, as well as to show that partnerships between ambulatory clinics, payers, and pharmacists are both sustainable and beneficial to all parties including, most importantly, the patients who receive better care for their complex chronic disease states. While this paper is descriptive in nature, work is ongoing to objectively measure the impact of the fellows on patients, providers, and third-party payers. A sampling of outcomes is presented, describing the impact of the pharmacist fellows’ efforts to improve medication management in primary care. Even with limited objective measures of success, we are able conclude that over the past 3 years, the fellowship has accomplished its aim of preparing fellows for future roles in ambulatory care, practice design, and academia while also demonstrating that a funding model aligning payers, clinics, and academia is sustainable.